The Price Impact and Service Quality for Consumer Purchasing Decisions at Indomaret Surya Sumantri 82 - Nurmartiani, Erika (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Purpose of this research is to know the price impact and service quality for consumer purchasing decisions at Indomaret Surya Sumantri 82. The research using 81 respondents as the research sample with SPSS25. The method using descriptif verificativ analysis with Quantitatif Approach. The instrument using 28 questions which are consist two questions on each variable. According to the analysis data result there is simple linier regretion similarity from the hipotesis result that the research indicate price variable and the service quality (X2) has F value count 641,616 and sig value 0.000 with F value table 3,115. With the result F count > F table and sig count < 0.005 it can be conclude that price simultanious and service quality affected purchase decision (Y). in this research also find that coefitien determination result has 85,4 % effect which mean the price impact and service quality 85,4 % and the rest is 14,6 % influence by other factor that doesn’t included in the research